2006
DOI: 10.1038/sj.onc.1209360
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase C delta inhibits Caco-2 cell proliferation by selective changes in cell cycle and cell death regulators

Abstract: PKC-d is a serine/threonine kinase that mediates diverse signal transduction pathways. We previously demonstrated that overexpression of PKC-d slowed the G1 progression of Caco-2 colon cancer cells, accelerated apoptosis, and induced cellular differentiation. In this study, we further characterized the PKC-d dependent signaling pathways involved in these tumor suppressor actions in Caco-2 cells overexpressing PKC-d using a Zn 2 þ inducible expression vector. Consistent with a G1 arrest, increased expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
52
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 141 publications
7
52
0
Order By: Relevance
“…Bcl-2 upregulation is related to the worst prognosis in colorectal tumorigenesis, while Bax expression tumors have a better prognosis (Cerda et al, 2006). Suppressed Bcl-2 and induced Bax expression are associated with altered apoptotic profiles in Caco-2 cells (Cerda et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Bcl-2 upregulation is related to the worst prognosis in colorectal tumorigenesis, while Bax expression tumors have a better prognosis (Cerda et al, 2006). Suppressed Bcl-2 and induced Bax expression are associated with altered apoptotic profiles in Caco-2 cells (Cerda et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…The protein kinase C family has crucial regulatory roles in cell growth and cell-cycle progression (Frey et al, 1997;Ashton et al, 1999;Jiang et al, 2002;Deeds et al, 2003;Cerda et al, 2006). Various studies have shown that PKC suppression generally inhibits cell-cycle progression, whereas PKC activation stimulates cellcycle progression (Frey et al, 1997;Deeds et al, 2003;Cerda et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have shown that PKC suppression generally inhibits cell-cycle progression, whereas PKC activation stimulates cellcycle progression (Frey et al, 1997;Deeds et al, 2003;Cerda et al, 2006). Therefore, we evaluated cell-cycle checkpoints after PKCy silencing in our GIST models (Figure 2c).…”
Section: Discussionmentioning
confidence: 99%
“…PKC␣ has been reported to increase cellular proliferation in hepatocellular carcinoma (40) and goblet cells (41), whereas PKC regulates Kit expression and induces proliferation in gastrointestinal stromal tumors (42). Conversely, PKC␤ and PKC␦ down-regulate proliferation of vascular smooth muscle cells (43,44), PKC␦ also inhibits Caco-2 cell proliferation (45).…”
Section: Discussionmentioning
confidence: 99%